Carbon nanostructured material for multiple protective masks - Kononko, I.V.; Boshytska, N.V.; Sergeev, V.P.; Klipov, V.D.; Kononko, N.V. (Reports of the National Academy of Sciences of Ukraine, 2021)
The complex of properties of the activated carbon fiber nanostructured material (AVVNM) developed by the authors as a filter layer of multiple protective face masks has been investigate. It is shown that AVVNM has a high ability to absorb the main environmental pollutants (phenol; metals Pb2+, Sr2+, Cu2+, Ni1+, Co2+, Al3+, Cs2+; chlorine derivatives; radioactive volatile decay products, etc.) and substances of the protein nature. It has been established that AVVNM exhibits the bacteriostatic properties which can be transformed into bacteri cidal ones by applying the biologically active substances on the material surface. It is proved that AVVNM meets the requirements for medical materials and can be recommended for the manufacture of protective masks.